Legal Study of Protection of Cultural Heritage Objectives in The Old Banten Tourism Area - Nurikah Nurikah; E Rakhmat Jazuli (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2022)
Based on the Decree of the Governor of Banten Number 437/Kep.160-Huk/2018 concerning the Zoning Determination of the Cultural Heritage Area of the Sultanate of Banten (Banten Lama). The existence of this decision has brought Banten Tourism currently experiencing significant development, especially in the tourist area. This happened after the Banten Provincial government carried out tourism development. The government has a role to synergize tourism development with the function of protecting cultural heritage objects and the community environment around the cultural heritage area of the Banten Lama, to create sustainable tourism based on the preservation of cultural heritage objects as the core area of cultural heritage. The role of the government is crucial to regulate efforts to manage cultural heritage objects as a form of legal study for the protection of tourism resources and to preserve cultural heritage objects as heritage tourism attractions in the Banten Lama area by establishing a core area of 172.58 hectares and a buffer area of 754.36 hectares. Also, involving the community is a tourism resource that must maintain the quality of the tourism environment to create Sapta Pesona and Tourism Awareness to create a conducive climate for the protection of cultural heritage objects in the Banten Lama Tourism area